Itikad Baik Pelaku Usaha Dalam Transaksi Jual Beli Online - Yunus Hitipeuw; Merry Tjoanda; Sarah Selfina Kuahaty (PATTIMURA Law Study Review, 2023)
ABSTRACT: Good faith is one of the efforts to provide legal protection to consumers in online buying and selling transactions. The research objective to be achieved by the author is how the good faith of business actors forms in online buying and selling transactions. And to find out and analyze how the responsibilities of business actors who do not have good intentions. This research is a problem approach using primary legal materials, tresier legal materials and secondary legal materials. The procedure for collecting legal materials used is library research. The processing and analysis of legal material is carried out using a normative legal research type with a qualitative descriptive method with a description of the problem and analyzing the legal material that has been collected. The results obtained are that the form of good faith in business conduct in online buying and selling transactions is a subjective form of good faith. Business actors are obliged to provide information regarding the goods they trade correctly and honestly as stipulated in Law Number 11 of 2008 Article 28 Paragraph (1) concerning electronic transactions. Therefore, the responsibility of business actors if they commit violations that cause harm to consumers in online buying and selling transactions is the obligation to compensate for losses that have been experienced by consumers in accordance with Law Number 8 of 1999 concerning consumer protection. the process of resolving disputes submitted by consumers can be resolved in two ways, namely by taking the court route or taking the route outside the court. The consumer protection law gives freedom to consumers who feel aggrieved to sue business actors through court but consumers also wish to resolve disputes with business actors through outside the court, so the consumer protection law provides a consumer dispute resolution agency (BPSK) which has the authority to handle consumer-related disputes.